Increase in antibiotic prescriptions in out of hours primary care in contrast to in hours primary care prescriptions: service evaluation in a population of 600,000 patients - Hayward, G; Fisher, R; Spence, G; Lasserson, D (Oxford University Press, 2016)
Objectives To describe the frequency and nature of antibiotic prescriptions issued by a primary care Out-of-Hours (OOH) service and compare time trends in prescriptions between OOH and In-hours primary care Methods We performed a retrospective audit of 496942 patient contacts with the Oxfordshire OOH primary care service. Comparison of time trends in antibiotic prescriptions from OOH primary care and in-hours primary care for the same population was made using multiple linear regression models fitted to the monthly data for out of hours prescriptions, out of hours contacts and in hours prescriptions between September 2010 and August 2014. Results Compared to the overall population contacting the OOH service, younger age, female sex, and patients who were less deprived were independently correlated with an increased chance of a contact resulting in prescription of antibiotics. The majority of antibiotics were prescribed to patients contacting the service at weekends. Despite a reduction in patient contacts with the OOH service (an estimated decrease of 486.5 monthly contacts each year (95%CI: −676.3 to −296.8) 5.0% of the average monthly contacts), antibiotic prescriptions from this service rose during the study period (increase of 37.1 monthly prescriptions each year (95%CI: 10.6 to 63.7) 2.5% of the average monthly prescriptions). A matching increase was not seen for in-hours antibiotic prescriptions; the difference between the year trends was significant (Z test, p = 0.002**). Conclusions We have demonstrated trends in prescribing which could represent a partial displacement of antibiotic prescribing from in hours to OOH primary care. The possibility that the trends we describe are evident nationally should be explored.